2021
DOI: 10.1073/pnas.2101296118
|View full text |Cite
|
Sign up to set email alerts
|

In situ three-dimensional spider web construction and mechanics

Abstract: Spiders are nature’s engineers that build lightweight and high-performance web architectures often several times their size and with very few supports; however, little is known about web mechanics and geometries throughout construction, especially for three-dimensional (3D) spider webs. In this work, we investigate the structure and mechanics for a Tidarren sisyphoides spider web at varying stages of construction. This is accomplished by imaging, modeling, and simulations throughout the web-building process to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…[40][41][42][43] Therefore, engineering the keratin fibril structure remains an attractive strategy to build regenerated wool keratin fiber (RWKF) with high mechanical performance for meeting the industrial manufacturing demand. [44][45][46][47] By virtue of its atomically thin structure and conspicuous mechanical performance, graphene has widely been used as a reinforcement for bio-composite fibers. [48][49][50][51][52][53][54][55][56] However, the underlying reinforcement mechanism, such as the graphene-induced conformation transitions and their effects on fiber mechanical behaviors, has been seldom discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43] Therefore, engineering the keratin fibril structure remains an attractive strategy to build regenerated wool keratin fiber (RWKF) with high mechanical performance for meeting the industrial manufacturing demand. [44][45][46][47] By virtue of its atomically thin structure and conspicuous mechanical performance, graphene has widely been used as a reinforcement for bio-composite fibers. [48][49][50][51][52][53][54][55][56] However, the underlying reinforcement mechanism, such as the graphene-induced conformation transitions and their effects on fiber mechanical behaviors, has been seldom discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40–43 ] Therefore, engineering the keratin fibril structure remains an attractive strategy to build regenerated wool keratin fiber (RWKF) with high mechanical performance for meeting the industrial manufacturing demand. [ 44–47 ]…”
Section: Introductionmentioning
confidence: 99%
“…Through research, it was found that the structure of the natural spider web in nature is composed of many radial silk threads protruding from the center and spiral silk threads around the center. The structure covers a wide area and is connected end to end, with excellent resonance sensing ability . When it is used in the structural design of the sensor, no matter where the strain occurs, it will be induced by structural resonance, so as to improve the sensitivity and stability of the sensor .…”
Section: Introductionmentioning
confidence: 99%
“…The structure covers a wide area and is connected end to end, with excellent resonance sensing ability. 35 When it is used in the structural design of the sensor, no matter where the strain occurs, it will be induced by structural resonance, so as to improve the sensitivity and stability of the sensor. 36 The structure of the spider web is refined and is difficult to make.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, spiders spin sticky, extensible, and translucent capture threads on stiff radial structural threads, which synergistically perform the missions of sensing approaching targets, capturing prey, and dissipating the kinetic energy. [ 1 , 2 , 3 , 4 ] Such integrated features greatly facilitate the advancements in shaping soft conductive materials as robotic counterparts that emulate the synergic functions of biological systems. [ 1 , 5 , 6 , 7 ] Compared with laborious and cost‐prohibitive mold‐making procedures, emerging 3D printing technologies offer unique advantages in the rapid design and fabrication of objects with complex geometries and functionalities beyond their bulky counterparts.…”
Section: Introductionmentioning
confidence: 99%